Not All Hope is Created Equal: Climate Action Research as a Source of Critical Hope - Mahoney, Tara; Grain, Kari (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Climate action research can be an emotionally and intellectually challenging space, given the magnitude of the climate crisis, the slow pace of progress, the existential weight of environmental degradation and isolation that results when researchers work and write alone. But action research for climate justice can also be an endeavour of hopefulness and vibrancy, wherein community connections and co-developed climate research data can forge meaningful changes for long term emotional and ecological sustainability. In this article, we examine the seven principles of critical hope (Redacted by Managing Editor, 2022) as a framework for identifying climate action research projects that exemplify critical hope. We draw on examples from both inside and outside the academy to explore how climate action research projects contribute to the communication and cultivation of critical climate hope.